Spatiotemporal dynamics and driving forces of water consumption patterns: insights from Jiangxi Province, China - Liu, Lina; Ouyang, Fen; Liu, Weilin; Zhou, Zhanxiong; Yin, Biaobiao (Frontiers in Environmental Science, 2025)
Investigating the spatiotemporal dynamics and underlying determinants of water consumption structure is of great importance for the strategic allocation of regional water resources and the promotion of economic and societal sustainability. This study, using Jiangxi province located in the Central China as a case study, employed information entropy and the center of gravity model to explore the spatiotemporal variations in water consumption patterns from 1999 to 2015. Additionally, the principal driving forces behind these changes were elucidated through factor analysis and grey correlation methods. The results indicated a consistent upward trajectory in Jiangxi’s total water consumption over the past two decades, with agricultural water accounting for the majority but gradually decreasing. The water consumption structure in Jiangxi province remained relatively stable, evolving towards a more equitable distribution. Notably, the spatial configuration of water consumption revealed obvious regional disparities, with high information entropy values predominantly in the northern areas, including Nanchang, Jingdezhen, and Jiujiang, while lower values in the southeastern regions. The epicenter of water consumption gradually shifted towards southern Jiangxi. Concurrently, the agricultural water use center migrated toward the northern, whereas the industrial and domestic water use centers moved southwards. Contrasting natural influences, socioeconomic factors, exemplified by population, urban population proportion, total output value of agriculture, forestry, animal husbandry, and fisheries, industrial output value, GDP, effective irrigation area, grain output value, and urban green coverage area, emerged as predominant, contributing to 67.7% of the alterations in water consumption patterns.